Comprehensive retrospect and future perspective on bacteriophage and cancer - Zhong Liping; Yu Sheng; Wu Yinhang; Song Yifei; Huang Jiaqun; Yu Xiaojian; Han Shuwen; Zhuang Jing (Virology Journal)
Abstract Background Researchers gradually focus on the relationship between phage and cancer. Objective To summarize the research hotspots and trends in the field of bacteriophage and cancer. Methods The downloaded articles were searched from the Web of Science Core Collection database from January 2008 to June 2023. Bibliometric analysis was carried out through CiteSpace, including the analysis of cooperative networks (country/region, institution, and author), co-citations of references, and key words.Visual analysis of three topics, including gut phage, phage and bacteria, and phage and tumor, was conducted. Results Overall, the United States and China have the most phage-related research. In terms of gut phage, the future research directions are “gut microbiome”, “database” and “microbiota”. The bursting citations explored the phage-dominated viral genome to discover its diversity and individual specificity and investigated associations among bacteriome, metabolome, and virome. In terms of phage and bacteria, “lipopolysaccharide” and “microbiota” are future research directions. Future research hotspots should mainly concentrate on the further exploration and application of phage properties. As for phages and tumors, the future research directions should be "colorectal cancer", "protein" and "phage therapy". Future directions are likely to focus on the research on phages in cancer mechanisms, cancer diagnosis, and cancer treatment combined with genetic engineering techniques. Conclusion Phage therapy would become a hot spot and research direction of tumor and phage research, and the relationship between phage and tumor, especially colorectal cancer (CRC), is expected to be further explored.